Ruminant livestock production and feed resources in the subhumid zone of Nigeria: Constraints and perspectives - Otchere, E.O.; Nuru, S. (1988)
The subhumid zone has a great potential in terms of carrying capacity to increase ruminant livestock production in Nigeria and tropical Africa in general. This paper reviews livestock distribution, land use constraints, feed resources and their effects on livestock productivity in the zone. Natural grasses and legumes need to be adequately managed to support expected livestock production, and alternative feed resources developed out of non-conventional materials currently available in Nigeria.